Synthesis, Characterization, and Optical Properties Study of Poly(o-aminophenol)/MWCNT Composite - Hussein, Hajar Ali; Mohammed, Mohammed Qasim; Al-Saymari, Furat Ahmed (Universitas Gadjah Mada, 2025)
In this paper, a functionalized multi-walled carbon nanotube (MWCNT) was prepared to be more active. Poly(o-aminophenol) was attached to MWCNT to create POAP:MWCNT nanocomposites using chemical polymerization. The polymerization process occurred in the acidic medium of hydrochloric acid and ammonium persulfate ((NH4)2S2O8) as an oxidizing reagent. The product nanocomposites were characterized via FTIR, XRD, SEM, and TGA. The effects of the addition on the structure, morphology, thermal, electrical, and optical properties of POAP and POAP:MWCNT were investigated. FTIR spectra revealed that carboxylic acid groups formed at the MWCNTs and the nanocomposite. As TGA confirmed, insertions of MWCNT within the polymer matrix led to apparent thermal amelioration. Furthermore, XRD spectra displayed the crystalline nature of POAP and nanocomposite materials. The SEM images of POAP:MWCNT show that the MWCNTs are dispersed within the structure of polymer chains, proving that the POAP:MWCNT composite was successfully prepared. The findings revealed that the electrical conductivity of poly(o-aminophenol) composite thin film was significantly enhanced by about 20000× due to doping by 1 wt.% MWCNT.